Prolegomena do twórczości Wawrzyńca Chlebowskiego. Stan badań i kierunki dalszych prac - Kuran, Michał (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2014)
Draws attention rich and varied occasional output of Chlebowski, who was a professional writer creating in the first half of the 17th century. However, former researchers accused him of plagiarism at the same time regarding him as a talented compiler. Researches on the Chlebowski’s output are going to lead to recognise his writing technique and expand knowledge about compilation and imitation.bbbFurthermore, the article presents the state of researches on the Chlebowski’s creativity starting from the oldest works of a bibliographic nature (end of the 18th and the 19th century) to the detailed studies, which concern the following issues: Zebrzydowski’s rebellion, political relations with the Grand Duchy of Moscow, hagiographic writings, political relations with Persia and the Ottoman Empire, images of natural disasters, the Tatar invasions and funeral writings. Moreover, the following directions for further studies have been indicated: recognising the biography of the poet; organising and enhancing the knowledge of his works; identification of the community, from the patronage of which Chlebowski benefited as a professional writer; redefinition of the relations between compilation, imitation and Chlebowski’s plagiarism; proving whose library resources the poet benefited from.